파킨슨병 환자의 통증에 대한 한의치료의 효과 : 후향적 연구 - 정혜선; 김하리; 김서영; 임태빈; 진철; 권승원; 조승연; 정우상; 문상관; 박정미; 고창남; 박성욱; et al. (대한한방내과학회지, 2020)
Objectives: To investigate efficacy of Korean medicine for patients with Parkinson's Disease (PD) with pain. Methods: We performed a retrospective review of the medical records for patients diagnosed with PD between 2012 and 2019 at Gangdong Kyung Hee University Korean Medicine Hospital in South Korea. Results: Twenty-two patients with King's Parkinson's Disease Pain Scale(KPPS) scores at least twice were analyzed for evaluating the efficacy of Korean medicine for pain treatment in PD. The mean total scores before and after Korean medicine treatment were 15.23±1 .01 and 9.2±8.7, respectively, and the mean difference between the before/after total scores was 6.0±5.8 (P<0.001). Specifically, the score of radicular pain was significantly decreased (P=0.048). Conclusions: These findings suggest that Korean medicine could be beneficial for reducing pain associated with PD. Clinical efficacy should be confirmed by further studies, such as large-sample cohort studies and randomized controlled trials to clarify the pathological pain relief mechanism and the analgesic effect of Korean medicine.